Application of heterogeneous photo-Fenton process for the mineralization of imidacloprid containing wastewater. Issue 5 (23rd February 2020) - Liu, Fuzhen; Ai, Jia; Zhang, Hui; Huang, Yao-Hui
ABSTRACT: The imidacloprid was mineralized by heterogeneous photo-Fenton process in a three-phase fluidized bed reactor using waste iron oxide as catalyst. The effects of catalyst loading, dosage of H2 O2 and pH were investigated to determine the optimal experiments conditions. The results revealed that TOC removal efficiency increases with an increase in H2 O2 dosage of up to 105.0 mM, an increase in catalyst dosage from 1.0 to 5.0 g L −1, and a decrease in pH from 5.0 to 3.5. Under the optimal conditions, 97.7% TOC removal was achieved in 6 h under 254-nm UV irradiation. Moreover, recycling experiments indicated that the waste iron oxide had a good stability and the TOC removal of pesticide yielded more than 80% under the fourth recycles. GRAPHICAL ABSTRACT: